2015
DOI: 10.1016/j.brainres.2014.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cellular cascades participate in long-term potentiation and in hippocampus-dependent learning

Abstract: Since its discovery by Bliss and Lomo, the phenomenon of long-term potentiation (LTP) has been extensively studied, as it was viewed as a potential cellular mechanism of learning and memory. Over the years, many signaling cascades have been implicated in its induction, consolidation and maintenance, raising questions regarding its real significance. Here, we review several of the most commonly studies signaling cascades and discuss how they converge on a common set of mechanisms likely to be involved in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 73 publications
5
39
0
Order By: Relevance
“…Thus the same biochemical machinery providing a molecular brake on LTP is involved in limiting the extent of learning of hippocampus-dependent tasks. We previously argued that such a mechanism could account for the beneficial effects of space training as opposed to massed training (Baudry et al, 2014; Shimizu et al, 2007; Wang et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Thus the same biochemical machinery providing a molecular brake on LTP is involved in limiting the extent of learning of hippocampus-dependent tasks. We previously argued that such a mechanism could account for the beneficial effects of space training as opposed to massed training (Baudry et al, 2014; Shimizu et al, 2007; Wang et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ influx has important implications for long‐term changes in synaptic efficacy as it triggers cascades of second‐messenger systems within the cell. This can lead to LTP or long‐term depression (LTD; a decrease in synaptic efficacy), depending on whether the change in intracellular Ca 2+ concentration is large or small (Baudry et al., ; Cormier, Greenwood, & Connor, ).…”
Section: Ltp Effects Evoked By Electrical Stimulation In Vitro and Inmentioning
confidence: 99%
“…As an important electrophysiological mechanism of learning and memory, LTP is a long-lasting increase in synaptic efficacy which follows high-frequency stimulation of afferent fibers (49). Our previous study showed that Aβ1-40-induced damage of late phase LTP, learning and memory were antagonized by Val 8 -GLP-1 (10).…”
Section: Discussionmentioning
confidence: 99%